TED Talks Video: A Technology to Teach Listening Skills - Fitri Novia; Ratna Nery; Ria Almukni (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
In the development of ICT, TED Talks Video as an authentic video can be used in listening classrooms. The use of real videos in listening comprehension lessons, like TED Talks, may enhance listening in English. Consequently, the study's goal was to determine whether or not students who were taught using the TED Talks Video application and those who were not had significantly different listening skills. It employed a quasi-experimental design. The eleventh graders at SMA Negeri 1 Pampangan participated in this study. The sample was selected by using a purposive sampling technique. The cloze test was used to obtain the data. A T-test was used to analyze the data. Based on the results of the independent sample t-test, the independent sample t-test result showed that the t-test obtained (2.825) was higher than the t-table (2.00) and ρ-value (0.000) was smaller than the α-value (0.05). It was shown that students who were taught using the TED Talks Video application had significantly better listening skills than those who were not. In conclusion, the TED Talks Video could be used to solve students' problems in listening skills. The TED Talks Videos can be used by English teachers as authentic listening materials and teaching aids.